Features of professional behaviour of specialists in social work with different educational levels - Dvaretskaya, Viktoriya A. (Journal of the Belarusian State University. Philosophy and Psychology, 2022)
The article examines the prerequisites for increasing the demand for specialists in social work in the labour market. The importance of vocational education is substantiated for ensuring high efficiency of the activities of specialists in the social sphere. The data of an empirical study of the type of behaviour and experience associated with activity, social norms of prosocial behaviour of specialists in social work with different educational levels are presented. According to the results of the study, social work specialists who do not have a specialised education are distinguished by a lower readiness to spend energy and energy resources in performing professional activities. Work has a lower subjective significance for them. At the same time, specialists who have not received an education in their specialty are inherent in: a lower level of professional aspirations, a less pronounced desire for excellence, an increased tendency to abandon activities in a situation of failure, less proactive problem-solving strategy, lower severity of a sense of success in professional activity, increased ability to maintain distance from work, decreased life satisfaction, a less intense feeling of social support and a lower level of formation of norms of prosocial behaviour.